(untitled) (International Journal of Scientific Trends, 2023)
Cybersecurity is critical in the field of information technology. Securing information has become one of today’s most difficult challenges. When we think of cyber security, the first thing that comes to mind is cybercrime, which is increasing at an alarming rate. Various governments and businesses are taking numerous steps to combat cybercrime. Aside from various measures, many people are still concerned about cyber security. This thesis mainly focuses on challenges faced by cyber security on the latest technologies. It also focuses on latest about the cyber security techniques, ethics and the trends changing the face of cyber security.